Геополитическая мысль России: история и современность - Danilchenko S. L. (Topical issues of archeology, ethnography and history (on the occasion of centenary of the birth of V.F. Kakhovsky and the diamond anniversary of Chu-vash Archeological Expedition), 2017)
What is common in the public consciousness of different periods of our history, why is the restoration of the interrupted continuity in the perception of our complex, but a great last?! Memories of the historical past are forced to think seriously about the greatness of Russia.
Keywords: русская история; социальная трансформация; политическая модернизация; союз славянских государств; developments in the field of Russian history; pre-revolutionary ideas and projects; the revival of Slavophilism; the Union of Slavic States; pan-Slavism; the creation of a pan-Slavic Union led by Russia; the change in the geopolitical situation; всеславянский союз; геополитическое положение